MRl and MRS hints for the differentiation of cerebellar multiple system atrophy from spinocerebellar ataxia type II - Hung-Chieh Chen; Li-Hua Lee; Jiing-Feng Lirng; Bing-wen Soong (Heliyon, 2024)
Background and objectives: The differentiation of spinocerebellar ataxia type II (SCA 2) from idiopathic multiple systemic atrophy of the cerebellar type (MSA-C) is often difficult in patients with cerebellar ataxia when molecular testing is not available. Besides genetic testing, magnetic resonance imagining (MRI) and magnetic resonance spectroscopy (MRS) prove to be beneficial. Nevertheless, the characteristics observed through radiology change as the disease advances. Different radiological criteria may be needed across different stages of the disease. This study aimed to assess the radiological characteristics of MSA-C or SCA 2 patients across various stages of the disease and to identify potential distinguishing factors. Methods: Between January 2000 and January 2020, a total of 390 patients, diagnosed with probable MSA-C according to the second consensus on MSA (317 cases) or with molecularly confirmed SCA 2 (73 cases), who had undergone at least one brain MRI and MRS targeting the cerebellar hemispheres, were enrolled in the study. The clinical parameters and neuroimaging features between these two diseases were compared and analyzed. Results: A greater occurrence of a pontine hot cross bun sign (HCBS), higher scores on the scale for the assessment and rating of ataxia, and reduced levels of cerebellar N-acetyl aspartate (NAA)/creatine (Cr), and cerebellar choline (Cho)/Cr were found in MSA-C patients as compared with SCA 2 patients at similar disease durations. For the patients with an HCBS, a cerebellar Cho/Cr level of <0.53 was indicative of the potential presence of MSA-C, with significant level of specificity (85.96%). Discussion: Discerning SCA2 from MSA-C using MRI and MRS appears to be plausible at various disease stages.